I think I can, I know I can? Success orientation in adult learner academic self-directedness - Botha, J. (South African Journal of Higher Education, 2021)
A Learning 2.0 milieu requires an active learner mindset, where the learner initiates and directs the learning experience. Consequently, adult learner academic self-directedness is essential for facilitating successful lifelong learning. Learner self-directedness is of specific importance in South African higher education, since only about 12 per cent of qualifying matriculants will continue to higher education, and of those, only about 6 per cent will qualify within 6 years. Adult learner self-directedness broadly consists of contextual (learning environment), cognitive (agency) and behavioural (self-management) elements. Although researchers agree that a fairly well-developed capacity for self-directedness is a requirement for successful ODeL studies, there is a lack of research on adult learner self-directedness in the South African ODeL context. The adult learner self-directedness scale (ALSDS) was developed to investigate adult learners in an ODeL context. The scale produced four factors describing adult learner self-directedness in, of which success orientation seems to be the most noteworthy.